Additional support services and the utilisation of teaching assistants in university settings: dissuading inclusive practice or improving academic outcomes?. Issue 1 (23rd March 2021) - Wray, Mike
Abstract : This paper examines the perceptions of staff within a university in the UK, of the role of teaching assistants and centrally located disability services. Staff were generally positive about support available although when communication had broken down this led to a lack of trust with centrally organised support. Staff were happy for support staff to be available within the classroom although this role was misunderstood. At times tensions arose around adjustments to classroom practices which were recommended by centrally located staff. Paradoxically, centrally organised support may have acted as a barrier to more inclusive teaching practice: whilst teaching staff often disagreed with recommendations for adjustments to teaching practice made by central staff they were nonetheless reluctant to take on the role of acting as the expert in these situations. Implications for practice and service delivery are discussed alongside suggestions for future research.